Experimental studies of heat exchange and aerodynamics of the efficient methods for heat exchange intensification - Bodnar, Liliya; Stepanov, Dmytro (Scientific Works of Vinnytsia National Technical University, 2015)
The paper estimates heat exchange intensification and pressure losses from the application of turbulizing inserts with round and rectangular openings in the round channel of gas-water heat exchanger. Experimental studies have been performed. Dependencies for intensified heat exchange calculation are proposed.